2001
DOI: 10.1002/path.946
|View full text |Cite
|
Sign up to set email alerts
|

MnSOD expression is less frequent in tumour cells of invasive breast carcinomas than inin situcarcinomas or non-neoplastic breast epithelial cells

Abstract: Manganese superoxide dismutase (MnSOD) is an antioxidant enzyme capable of neutralizing superoxide anion molecules. In previous studies it has been suggested to suppress both tumour proliferation and apoptosis. This study investigated 65 invasive, 50 in situ and 19 benign hyperplastic breast lesions for its immunohistochemical expression. MnSOD expression was also tested with in situ hybridization. To study cell proliferation, apoptosis and their association with MnSOD expression the neoplastic breast lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 38 publications
2
62
0
1
Order By: Relevance
“…Molecularly, the MnSOD Ala/Ala genotype causes an amino acid substitution from valine (Val) to alanine (Ala),which reduces MnSOD enzymatic activity and its ability to remove ROS (Sutton et al, 2003). The latter was confirmed to play an important role in regulating cell proliferation and carcinogenesis (Soini et al, 2001). Studies on human tissue specimens showed that MnSOD was absent or reduced in breast cancer (Soini et al, 2001) and prostate cancer (Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Molecularly, the MnSOD Ala/Ala genotype causes an amino acid substitution from valine (Val) to alanine (Ala),which reduces MnSOD enzymatic activity and its ability to remove ROS (Sutton et al, 2003). The latter was confirmed to play an important role in regulating cell proliferation and carcinogenesis (Soini et al, 2001). Studies on human tissue specimens showed that MnSOD was absent or reduced in breast cancer (Soini et al, 2001) and prostate cancer (Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that MnSOD expression is down regulated in breast carcinoma cells compared to their normal cells of origin. 3 To query the molecular mechanism(s) for differential MnSOD expression in normal versus tumor we used the breast carcinoma cell line MDA-MB-435 and the immortalized breast epithelial line MCF-10A. First, we used quantitative real time RT-PCR to compare the levels of SOD2 transcript in these cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MnSOD expression is altered in primary breast tumors compared to the tissues from which they arise. 3 Our study has identified one region of the SOD2 promoter that can be analyzed to compare CpG methylation between primary breast tumor samples and isogenic normal breast epithelial cells. Such studies are currently being undertaken in our laboratory to further elucidate the role epigenetic regulation of SOD2 plays in human breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations